Angular Distribution of Delta Electrons in SAGE Spectrometer using Geant4 - Ali, F. A.; Hassan, H. J. (Sulaimani Journal for Pure and Applied Sciences, 2018)
This simulation work is intended to describe the angular distribution of (δ) electrons in a spectrometer that is designed for simultaneously measuring gamma-rays and electrons called SAGE Spectrometer using the Geant4 simulation toolkit. The angular distributions were identified for various target materials including lead, gadolinium, tin, aluminium and carbon. In heavy ion atom collision, the direct ionization of the target elements and the scattering of electron due to the Two-Centre Coulomb forces are the dominant contributions. The direction of (δ) electrons produced in a heavy ion collision hitting a heavy element target is strongly focused in the forward and backward directions with a large suppression at perpendicular angles. For light element targets the (δ) electrons are almost entirely forward focused. This indicates that the distributions are (Z) dependent. The main features of the (δ) electrons coming from SAGE spectrometer are characterized by looking at their angular distributions produced from a reaction between a Ca48 ion beam and a lead target.
Keywords: SAGE Spectrometer; delta electron Angular distribution